Trends and research mapping of mathematical mindset publications: A bibliometric analysis using Vosviewer - Yusuf Adhitya; Nurmala Setianing Putri; Bill Chairy Rizki Bustaren; Jay Fie Paler Luzano (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
In addition to the theory and implementation, the description of research trends and the direction of development of mathematical mindset research still needs to be explored. The study aims to find trends and mapping from the mathematical mindset research development. The method used is bibliometric with the help of MS Excel and VosViewer. The metadata is 995 articles indexed by Google Scholar from 2019 to 2025, obtained from Publish or Perish by entering the keyword